Pelatihan Penataan Hijab Pengantin Muslim Modern Untuk Menumbuhkan Jiwa Wirausaha pada Siswa Double Track di SMA Progresif Bumi Shalawat - Nia Kusstianti; Dewi Lutfiati; Arita Puspitorini; Dindy Sinta Megasari; Sri Usodoningtyas; Sri Dwiyanti (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Hijab styling training for modern Muslim brides was given to 23 double track students at SMA Progresif Bumi Shalawat to foster an entrepreneurial spirit. The training was carried out using a direct learning model with a demonstration method. Assessment of training results was carried out through direct observation by two observers from Unesa. The training results were obtained for neatness of the hijab 82.4% Very good, 17.4% Good, Difficulty Level of Styling; 47.8%) Very good 52.2% Good, Suitability to Face Shape 73.9% Very good and 26.1% Good. The response of participants to the training was obtained, almost all students gave a positive response and wanted to hold another training with a different theme. In addition to being able to increase creativity through the training provided, Unesa through the Makeup Education Study Program can establish good cooperation with SMA Progresif Bumi Shalawat.